Comparison of 0.5% lignocaine versus 0.2% ropivacaine in intravenous regional anesthesia (Bier’s block) in upper limb surgeries (Panacea Journal of Medical Sciences, 2024)
Background: Ropivacaine is a new local anesthetic. it is long acting and it will not affect heart. Its use for epidural anesthesia and blocks for the peripheral nerves is well established. But, data is limited on use and effects of ropivacaine in IVRA.Objective: To study if Ropivacaine is a better alternative to Lignocaine in Intravenous Regional Anesthesia with respect to efficacy and post-operative analgesia.Materials and Methods: This was a prospective, double-blind, randomized comparative study carried out among 60 patients of ASA grade 1 or 2 of either sex and age 18-60 years admitted for elective upper limb surgeries. Randomization was done based on computer generated random numbers. Group 1- 30 patients received 0.5% Lignocaine - 40ml and Group 2- 30 patients received 0.2% Ropivacaine – 40ml.Results: Mean age, mean duration for surgery, weight and Proximal Tourniquet Tolerance time (min) were similar in two groups (p>0.05). Motor regression time (min), Onset of action (min), Sensory regression time (min), Rescue analgesia (min) was significantly more in group-2 patients compared to group-1 patients (p Conclusion: Ropivacaine is better than lignocaine. The analgesia i.e. during surgery and after surgery, motor blockade were better with ropivacaine than lignocaine and at the same time there were no complications. Hence, IVRA with ropivacaine should be used.